2023
DOI: 10.1021/acs.energyfuels.3c00499
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen/Syngas Production from Different Types of Waste Plastics Using a Sacrificial Tire Char Catalyst via Pyrolysis–Catalytic Steam Reforming

Abstract: Single plastics and mixed waste plastics from different industrial and commercial sectors have been investigated in relation to the production of hydrogen and syngas using a pyrolysis–catalytic steam reforming process. The catalyst used was a carbonaceous char catalyst produced from the pyrolysis of waste tires. Total gas yields from the processing of single plastics were between 36.84 and 39.08 wt % (based on the input of plastic, reacted steam, and char gasification) but those in terms of the gas yield based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…HDPE, PP, and PS were obtained from Regain Polymers Limited, Castleford, U.K., while LDPE and PET were purchased from Sigma-Aldrich. All of the plastics were subjected to ultimate analysis and proximate analysis, and the results have been reported in our previous work …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HDPE, PP, and PS were obtained from Regain Polymers Limited, Castleford, U.K., while LDPE and PET were purchased from Sigma-Aldrich. All of the plastics were subjected to ultimate analysis and proximate analysis, and the results have been reported in our previous work …”
Section: Methodsmentioning
confidence: 99%
“…To address this problem, the use of pyrolysis char as a catalyst for the catalytic steam reforming process has been the topic of recent studies; for example, biochar, coal char, and tire char have been proposed as potential catalysts. The advantages of pyrolysis chars as catalysts have been reported as their high surface area and pore volume, and the presence of abundant surface functional groups also regarded as low-cost catalysts. ,, In addition, the metals present, as the ash component of the char, can act as catalysts to enhance hydrogen and syngas yield via the reforming and water–gas shift reactions . For example, alkaline metals such as K, Na, and Ca found in biochars and transition metals such as Fe, Co, Cu, and Zn found in coal and tire chars have been reported as active metals for the promotion of steam reforming and water–gas shift reactions. Yao et al investigated the use of biochar produced from the pyrolysis of different biomass types as a support for nickel and reported that the texture and compositional characteristics of the biochar catalysts promoted the reforming of pyrolysis volatiles derived from biomass. Liu et al used biochar from the pyrolysis and steam activation of biomass and also showed that the presence of O-containing functional groups in the biochar promoted the steam reforming process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysts with excellent catalytic performance suitable for low-temperature biomass tar steam reforming generally have special characteristics, such as small and uniformly dispersed active metal particles, strong metal–support interaction (MSI), and good carbon-resistance. For example, Ren and Liu et al recently developed Ni/Mg–Al hydrotalcite and Ni/ZSM-5 catalysts and applied them to the steam reforming of toluene (SRT). They found that Ni/Mg–Al hydrotalcite with an average Ni size of 7.0 nm and a high reducibility of 96%, as well as Ni/ZSM-5 with an average Ni size of 15.2 nm, exhibited excellent catalytic performance with the toluene conversion reaching nearly 90% at 600 °C.…”
Section: Introductionmentioning
confidence: 99%